Cars’ sales systems improvement on the global market - Савич, Олександр Петрович (Technology audit and production reserves, 2015)
The modern car market is the basis of the global economy. Car`s sales make strong influence at economic growth and crisis in the global economy. The car market is one of more competitive market among others and just here all innovations and technologies as in management as in marketing and production are implemented. Car market is cyclic very much by its nature. So, car market has suffered crisis for several time during last 15 years. And such car makers as Chrysler and SAAB could not managed to survive demand`s fluctuation. The negative trends of sales are to be seen even now. Therefore car producers have to change and develop its sales system with the aim to increase competitiveness. The classic cars` sales schemes which have been used since 30th of the last century as well as new sales channels have been viewed at the article. It is realized that the classis cars` sales system is changing in the modern time. Cars are becoming more complicated. New sales channels have been researched and proposed to be realized. It is offered to upgrade the cars` sales system and develop new sales channels. It will help to sell more active at target segments and allows specialized dealers to focus at clients.